Comparative Effectiveness of Antidiabetic Drugs as an Additional Therapy to Metformin in Women with Polycystic Ovary Syndrome: A Systematic Review of Metabolic Approaches - Maryam Heidarpour; Mehrzad Mojarad; Sadegh Mazaheri-Tehrani; Ali Kachuei; Arash Najimi; Davood Shafie; Hassan Rezvanian (International Journal of Endocrinology)
Background. Metformin is commonly prescribed to treat polycystic ovary syndrome (PCOS) patients, but in some cases, it may not be effective even at high doses or may cause intolerable side effects. Therefore, recent studies have examined the impact of combining metformin with other antidiabetic medications. Methods. A systematic search was performed in Scopus, PubMed, Web of Science, and Embase up to 30 June 2023. All interventional studies that assessed the efficacy of different antidiabetic agents were included. Results. Among the 3488 records found in the primary search, 16 papers were included. Our study showed that dipeptidyl peptidase-4 inhibitors (DPP4i) had the most significant impact on glycemic profile, while thiazolidinediones (TZDs) had the most influence on lipid levels. However, it was observed that patients taking only metformin experienced a greater increase in high-density lipoprotein cholesterol (HDL-C) levels. Glucagon-like peptide-1 receptor agonists (GLP1RAs) effectively modified various anthropometric measurements, such as weight, body mass index, waist circumference, and waist-to-hip ratio. The effects of different antidiabetic drugs on hormone levels were inconclusive, although testosterone levels were more affected by GLP1RA, sodium-glucose cotransporter-2 inhibitors (SGLT2i), and TZDs. None of the combined therapies showed a significant change in blood pressure. Conclusion. Since PCOS is a metabolic disorder, choosing the best combination of antidiabetic drugs in the clinical course of PCOS patients will be very important. Today, it seems that we need a new metabolic approach for better treatment of the metabolic aspects of these patients.